Walnut SSR raw data, Central Asia - Gaisberger, Hannes; Legay, Sylvain (Bioversity International and the International Center for Tropical Agriculture, 2020)
Between September 2013 and September 2015, samples of Juglans regia L. were collected from three countries in Central Asia: Tajikistan, Uzbekistan, and Kyrgyzstan. We selected 360 sample individuals from wild tree population (four populations of 30 individuals in each country) and 270 samples from cultivated populations from home gardens (three populations of 30 individuals in each country). Within each wild population, a systematic sampling experimental design has been chosen to collect the 30 individual adult trees with at 50m regular intervals. From each sampled tree, three leaves were collected and stored in silica for subsequent genetic analyses conducted at the Luxembourg Institute of Science and Technology (LIST). Genomic DNA was extracted from ground silica dried leaf material using the NucleoSpin Plant II kit (Macherey-Nagel). All SSR loci were PCR amplified following Pollegioni et al. (2014) and multiplex PCR products analyzed on an ABI3500 Genetic Analyser (Life Technologies, Waltham, MA). Subsequently, fragment analysis was conducted using the Genemapper 5.0 software. ND: No Data after re-extraction and re-amplification of the sample.